Ethics of narrative : essays on history, literature, and theory, 1998-2007 - White, Hayden 1928-2018; Doran, Robert 1968-; Butler, Judith 1956- (New York, USA: Cornell University Press, 2022)
"The first in a two-volume anthology of Hayden White's uncollected essays from the last two decades of his life, revealing White as a public intellectual. It places White's thought in context, explaining its major themes, sources, and frames of reference, and features five previously unpublished lectures as well as more complete versions of several published essays"--
v.1. The problem with modern patriotism -- Symbols and allegories of temporality -- The discourse of Europe and the search for a European identity -- Catastrophe, communal memory, and mythic discourse: the uses of myth in the reconstruction of society -- Figura and historical subalternation -- The westernization of world history -- On transcommunality and models of community -- Anomalies of the historical museum or, history as utopian space -- Figural realism in witness literature: on Primo Levi's Se questo è un uomo -- The elements of totalitarianism: on Hannah Arendt -- The metaphysics of western historiography: cosmos, chaos, and sequence in historiological representation -- Historicality as a trope of political discourse: rhetoric, ethics, politics -- Exile and abjection -- The dark side of art history: on melancholy -- Against historical realism: a reading of Leo Tolstoy's War and peace
Includes bibliographical references and index.
Keywords: Historiography; Literature and history; History -- Philosophy; Essays